I. Discovery and development of nickel-catalyzed 1,2-dicarbofunctionalization reactions of alkenes II. Synthesis and reactivity of nucleophilic calcium fluoride complexes with oxygenic ligand frameworks - Apolinar, O (2024)
Part I. Discovery and Development of Nickel-Catalyzed 1,2-Dicarbofunctionalization Reactions of Alkenes.